Draft Annual Plan 1990-91 Union Territory of Chandigarh - Planning Commission (Planning Commission, 1990)
Chandigarh is a small Union Territory without legislature, and is spread over an area of 114 Sq. Kms., comprising the city of Chandigarh, Manimajra. Notified Area. Committee and 22 villages. The present population of this Union Territory is about 7 lacs and islikely to go upto 7.50 lacs by 1990. the smalt rural belt is gradually diminish ing further with the acquisition of more land for the expansion of the city. Since Chandigarh was never conceived as an industrial town, no major industry could be set up here. However, a number of villagesand small industries have come up during the past years. All the 22 villages in this Union Territory have been provided with modern amenities such as pucca roads, electrification piped water supply, bus service, schools etc.
Union Territory of Chandigarh